Promoting pro-environmental behaviours through induced hypocrisy. (March 2019) - Odou, Philippe; Darke, Peter; Voisin, Dimitri
In the field of ethical consumption, research in recent years has attempted to explain the gap between principles and actual behaviour. Three experimental studies show that when the contradiction between what individuals say and what they do is made salient in the field of environmental protection, that is to say in a situation of induced hypocrisy, they indirectly reduce the resulting cognitive dissonance by being more altruistic towards associations that act for the environment but not towards humanitarian associations. This effect of induced hypocrisy fades as individuals become less vulnerable to the threat to the self by affirming values that are important to them.